The Significance of Software Quality: A Comprehensive Analysis - Ward, Prof. Frederick (Journal of Science & Technology, 2022)
Software quality is a critical aspect of the software development life cycle, influencing the success of software applications and systems. Software quality is a critical factor in ensuring the success of software projects [1]. This research article explores the importance of software quality, delving into its various dimensions and the far-reaching implications it has on businesses, end-users, and the overall software ecosystem. We discuss the challenges associated with poor software quality and present compelling reasons why prioritizing and maintaining high standards in software development is paramount. By eliminating waste and improving efficiency through continuous improvement initiatives, the company achieved notable cost reductions [2]